If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(x-3)-26=11
We move all terms to the left:
-5(x-3)-26-(11)=0
We add all the numbers together, and all the variables
-5(x-3)-37=0
We multiply parentheses
-5x+15-37=0
We add all the numbers together, and all the variables
-5x-22=0
We move all terms containing x to the left, all other terms to the right
-5x=22
x=22/-5
x=-4+2/5
| 6p-12=3p | | 5x-48=168 | | x×2=6,x= | | 4x-8=24x= | | x-3=-6x= | | 4x+24=8,x= | | x+3=8,x= | | 1.25x=-1.875,x= | | 3x=2(x+1)-x-2 | | 2x÷5=4,x= | | 9−v=12 | | x÷3=4,x= | | 2(g−3)−4=2 | | 3(v−6)=6 | | (3-2d)4+5=15 | | 14d+26=11d | | 9-3r=-4(r-4) | | 5(x+2)=5x+12 | | 3(-6-v)=4+8v | | 2(p+10)−7=-7 | | 16-2x2=0 | | 5m-3(m+3)=11+6m | | -3+3(1+4m)=-m-13 | | 135=x-125 | | -24+2n=-7(-8+2n) | | x*2=-12= | | 41x2-20x+84=0 | | 2x-x=3-5 | | -39-8x=3(1-5x) | | q−1/2=3 | | 3(2x+5)=3(x+3) | | m−4/2=2 |